Gestión administrativa en el Departamento de Servicios Públicos en la ciudad de Babahoyo - Perez Quijano, Danny Xavier (2021)
The Autonomous Municipal Decentralized Government of the Babahoyo Canton, as part of its projection for the development of the city, has a public services department, which is in charge of planning, advising, managing and improving the health, hygiene and environmental sanitation conditions of the canton and its parishes. The main objective of this case study is to determine the functioning of the administrative management of the department of public services of the City of Babahoyo, in order to know if such management is being carried out or if, on the contrary, there are certain shortcomings that may be affecting employees and all Babahoyo citizens in a general way.